Neurolaw Advances in Neuroscience, Justice & Security - Ligthart, Sjors; van Toor, Dave; Kooijmans, Tijs; Douglas, Thomas; Meynen, Gerben (Palgrave Studies in Law, Neuroscience, and Human Behavior, 2021)
This book aims to contribute to the ongoing debate on neuroscience, justice, and security, by examining how neuroscience could contribute to fair and more effective criminal justice systems, and how both neurosci entific insights and information can be integrated into criminal law in a way that respects fundamental rights and moral values. The first part approaches these questions from a legal perspective, followed by ethical accounts in part two.